APLIKASI GELATIN KULIT KAMBING BLIGON SEBAGAI BAHAN DASAR DALAM FORMULA TERHADAP SIFAT-SIFAT CANGKANG KAPSUL OBAT - Muhammad Irfan Said; Suharjono Triatmojo; Yuny Erwanto; Achmad Fudholi (Jurnal Ilmu dan Industri Peternakan, 2014)
ABSTRACT. Shell of commercial capsule (CC) is generally made of gelatin from skin or bone of cows and pigs, while the capsule shell made from goat skin is not widely publicized. This study aims to determine the properties shell of hard capsules of gelatin from Bligon goat skin. The gelatin from male Bligon goat skin (GBGS), glycerol, MgCO, tapioca and sago starch were used as main materials, and than shell of CC number zero was used as a control. The Simplex Lattice Design method was used to prepare formula of shell. Anumber 10 g of GBGS + 9 g of glycerol + 22 mg of MgCO3 + 5.5 mg of tapioca starch + 72.1 mg of sago starch were used as formula of capsule shell. An uniformity weight of shell (average, deviation and coefficient of variation) and than disintegration time (coefficient of variation) were used as parameter of this study. The data of this study were analyzed by descriptively with shell of CC as control. The results showed that the average of weight and disintegration time of shell from GBGS higher than CC. The solubility (dissolution) of active ingredient (paracetamol) on shell from GBGS has maximum percentage of 95.85% with dissolution in the thirty minute, and therefore has been declared the eligibility criteria of dissolution by the British Pharmacopeae 2007.